Chronic Dietary Vitamin A Supplementation Regulates Obesity in an Obese Mutant WNIN/Ob Rat Model - Shanmugam M. Jeyakumar; Ayyalasomayajula Vajreswari; Nappan Veettil Giridharan (2006)
Abstract Objective : To understand the possible role of chronic dietary high vitamin A supplementation in body weight regulation and obesity using a novel WNIN/Ob obese rat model developed at the National Centre for Laboratory Animal Sciences of National Institute of Nutrition, India. Research Methods and Procedures : Thirty‐six 7‐month‐old male rats of lean, carrier, and obese phenotypes were broadly divided into two groups; each group was subdivided into three subgroups consisting of six lean, six carrier, and six obese rats and received diets containing either 2.6 or 129 mg vitamin A/kg of diet for 2 months. Body weight gain, food intake, and weights of various organs were recorded. Adiposity index and BMI were calculated. Serum and liver retinol and brown adipose tissue (BAT)‐uncoupling protein1 (UCP1) mRNA expression levels were quantified. Results : Chronic feeding of high but non‐toxic doses of vitamin A through diet significantly reduced ( P ≤ 0.05) body weight gain, adiposity index, and retroperitoneal white adipose tissue mass (without affecting food intake) in obese rats compared with their lean and carrier counterparts. In general, vitamin A treatment significantly improved hepatic retinol stores ( P ≤ 0.05) in all phenotypes without affecting serum free retinol levels. However, augmented BAT‐UCP1 expression was observed only in carrier and obese rats (whose basal expression was low). Discussion : Our data suggest that chronic dietary vitamin A supplementation at high doses effectively regulates obesity in obese phenotype of the WNIN/Ob strain, possibly through up‐regulation of the BAT‐UCP1 gene and associated adipose tissue loss. However, in vitamin A‐supplemented lean and carrier rats, changes in adiposity could not be related to BAT‐UCP1 expression levels.